To what Extent do Fiscal Regimes Equalize Opportunities for Income Acquisition Among citizens? - John E. Roemer; Rolf Aaberge; Ugo Colombino; Johan Fritzell; Stephen P. Jenkins; Ive Marx; Marianne Page; Evert Pommer; Javier Ruiz-Castillo; Maria Jesus SanSegundo; Torben Tranaes; Gert G. Wagner; et al. (Statistics Norway, Research Department, 2000)
This project employs the theory of equality of opportunity, described in Roemer's book (Equality of Opportunity, Harvard University Press, 1998), to compute the extent to which tax-and-transfer regimes in ten countries equalize opportunities among citizens for income acquisition. Roughly speaking, equality of opportunity for incomes has been achieved in a country when it is the case that the distributions of post-fisc income are the same for different types of citizen, where a citizen's type is defined by the socio-economic status of his parents. Intuitively, a country will have equalized opportunity if the chances of earning high (or low) income are equal for citizens from all family backgrounds. Of course, pre-fisc income distributions, by type, will not be identical, as long as the educational system does not entirely make up for the disadvantage that children, who come from poor families face, but the tax-and-transfer system can play a role in rectifying that inequality. We include, in our computation, two numbers that summarize the extent to which each country's current fiscal regime achieves equalization of opportunities for income, and the deadweight loss that would be incurred by moving to the regime that does.
Keywords: D63; H00; 330